Implementation of Health Services for Prisoners with Disabilities at the Class I Correctional Institution of Surabaya - Sukananda, Arysman Pratama; Herisasono, Adi; Vitrianingsih, Yeni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study explores the implementation of health services for prisoners with disabilities in Surabaya Class I Penitentiary. The background of this study is rooted in the need to understand how the health care system functions for prisoners with disabilities, who often face unique challenges in the correctional environment. The purpose of this study was to evaluate the effectiveness of health services provided, identify existing barriers, and provide recommendations for improvement. The research method used was a qualitative approach with in-depth interviews with health workers, prisoners with disabilities, and direct observation of health facilities and services in the prison. The results of the study indicate that although there have been significant efforts to meet the health needs of prisoners with disabilities, there are still a number of obstacles such as limited accessibility of facilities, lack of training for health workers on special needs, and lack of coordination between related parties. The conclusion of this study is that, although health services have improved, further adjustments are needed in terms of accessibility and training to improve the quality of services for prisoners with disabilities. Additional support and increased coordination between agencies will be essential to ensure better fulfillment of health rights in Surabaya Class I Penitentiary.